2012
DOI: 10.1016/s0924-9338(12)75146-5
|View full text |Cite
|
Sign up to set email alerts
|

P-979 - Psychiatric morbidity among internally displaced persons (IDPs) of sindh

Abstract: Introduction: Devastating floods from July to September 2010 broke all previous records of havoc caused by natural disasters in Pakistan. Flood caused 20 million people to loose their homes, profession and community making them internally displaced. Devastating consequences are still continuous within the country. Objectives: To find out the prevalence of anxiety, depression and post-traumatic stress disorder among flood affected Internally Displaced Persons (IDPs) of Sind. Aims: To find out psychiatric morbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The remaining studies did not directly explore the association of interest, solely reporting mental disorder prevalence rates among those exposed to a climate change or climate disaster event. Rahman et al 51 and Solangi et al 52 both studied flood-related displacement, a broader climate change-related exposure. The former study reported a 9% prevalence of PTSD and 44% prevalence of depression, 51 while the latter reported a 32% prevalence of PTSD and 39% prevalence of depression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining studies did not directly explore the association of interest, solely reporting mental disorder prevalence rates among those exposed to a climate change or climate disaster event. Rahman et al 51 and Solangi et al 52 both studied flood-related displacement, a broader climate change-related exposure. The former study reported a 9% prevalence of PTSD and 44% prevalence of depression, 51 while the latter reported a 32% prevalence of PTSD and 39% prevalence of depression.…”
Section: Resultsmentioning
confidence: 99%
“…The former study reported a 9% prevalence of PTSD and 44% prevalence of depression, 51 while the latter reported a 32% prevalence of PTSD and 39% prevalence of depression. 52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation